An Arab Adolescent with Multisystem Inflammatory Syndrome Associated with COVID-19: A Report from Syria - Jaafer Zaino (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Multisystem inflammatory syndrome in children (MIS-C) is a rare and critical condition that affects children following exposure to severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) infection, leading to multiorgan dysfunction and shock. MIS-C has been reported from different parts of the world but rarely from Arab countries. In this report, we describe a 15-year-old Arab boy who was admitted to the ICU during the surge of Coronavirus transmission in Syria with a clinical picture consistent with MIS-C, including high-grade fever, gastrointestinal symptoms, rash, multiorgan dysfunction, and shock. Laboratory profile showed significant elevation of inflammatory markers, negative SARS-CoV-2 RT-PCR testing but positive serologic testing for SARS-CoV-2. The patient received intravenous immunoglobulins (IVIG) and glucocorticoids with remarkable cardiac improvement and significant alleviation in inflammatory markers. To our knowledge, this is the first reported case of MIS-C from Syria, which adds to the epidemiological data about this new syndrome.